The Use of Heptamethine Cyanine Dyes as Drug-Conjugate Systems in the Treatment of Primary and Metastatic Brain Tumors - Cooper, Elizabeth; Choi, Peter J.; Denny, William A.; Jose, Jiney; Dragunow, Mike; Park, Thomas I.-H. (Frontiers in Oncology, 2021)
Effective cancer therapeutics for brain tumors must be able to cross the blood-brain barrier (BBB) to reach the tumor in adequate quantities and overcome the resistance conferred by the local tumor microenvironment. Clinically approved chemotherapeutic agents have been investigated for brain neoplasms, but despite their effectiveness in peripheral cancers, failed to show therapeutic success in brain tumors. This is largely due to their poor bioavailability and specificity towards brain tumors. A targeted delivery system might improve the efficacy of the candidate compounds by increasing the retention time in the tumor tissue and minimizing the numerous side effects associated with the non-specific distribution of the chemotherapy agent. Heptamethine cyanine dyes (HMCDs) are a class of near-infrared fluorescence (NIRF) compounds that have recently emerged as promising agents for drug delivery. Initially explored for their use in imaging and monitoring neoplasms, their tumor-targeting properties have recently been investigated for their use as drug carrier systems. This review will explore the recent developments in the tumour-targeting properties of a specific group of NIRF cyanine dyes and the preclinical evidence for their potential as drug-delivery systems in the treatment of primary and metastatic brain tumors. Highlighting the challenges in neurooncology, this review puts forward a unique drug-delivery system to re-invigorate the possible use of existing anti-cancer agents, previously neglected for their lack of permeability and specificity, for the treatment of brain tumors and metastases.